Introduction of innovative technologies in vocational education under the conditions of informatization of society: problems and prospects - Truba, H.; Radziievska, I.; Sherman, M.; Demchenko, O.; Kulichenko, A. K.; Havryliuk, N.; Куліченко, Алла Костянтинівна (My University, 2023)
The use of modern innovative technologies in vocational education is an important challenge of today through the prism of technological development. The aim of the article is to analyze the introduction of innovative technologies in vocational education under the conditions of informatization of society, to determine the problems and prospects of this process. The article is written through the prism of using comparative analysis, predictive method, modeling method. The empirical study involved 170 teachers from 28 to 74 years old and the corresponding difference in professional experience from 1 to 35 years. The results demonstrated the effectiveness and prevalence of the use of information technology in professional education. Based on the materials worked out, it was proved that only 2.28% of teachers had never used information technology in their work. The most widespread in the use of appropriate computer technology and software, electronic platforms, and online courses. As a result of the analytical material, the general problems that may arise in their use in professional education are highlighted. First of all, we are talking about the insufficient level of training of teachers, trainers, etc. lack of necessary facilities, lack of means to assess the effectiveness, low salaries of teachers. The conclusions also summarize the importance of addressing continuing education as an innovative educational technology that allows you to take into account the dynamics of digital technology in the training of specialists.
Keywords: Vocational education; Information technology; Innovation; Prospects